2007
DOI: 10.1128/mcb.00719-07
|View full text |Cite
|
Sign up to set email alerts
|

Replication in Hydroxyurea: It's a Matter of Time

Abstract: Hydroxyurea (HU) is a DNA replication inhibitor that negatively affects both the elongation and initiation phases of replication and triggers the "intra-S phase checkpoint." Previous work with budding yeast has shown that, during a short exposure to HU, MEC1/RAD53 prevent initiation at some late S phase origins. In this study, we have performed microarray experiments to follow the fate of all origins over an extended exposure to HU. We show that the genome-wide progression of DNA synthesis, including origin ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
248
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 212 publications
(276 citation statements)
references
References 41 publications
23
248
1
2
Order By: Relevance
“…Moreover, in a given population of cells, each origin has a distinct probability of activation, which is defined as origin efficiency. Although population studies have demonstrated that each origin has distinct timing and efficiency properties (Raghuraman et al 2001;Yabuki et al 2002;Alvino et al 2007;McCune et al 2008;McGuffee et al 2013;Müller et al 2014), DNA combing experiments have shown that DNA replication occurs stochastically in individual cells and, therefore, is not as deterministic as population analyses suggest (Patel et al 2006;Czajkowsky et al 2008). These findings can be reconciled by averaging the heterogeneous replication kinetics of a large number of cells, which recapitulates the observed data from population studies (Czajkowsky et al 2008).…”
supporting
confidence: 66%
“…Moreover, in a given population of cells, each origin has a distinct probability of activation, which is defined as origin efficiency. Although population studies have demonstrated that each origin has distinct timing and efficiency properties (Raghuraman et al 2001;Yabuki et al 2002;Alvino et al 2007;McCune et al 2008;McGuffee et al 2013;Müller et al 2014), DNA combing experiments have shown that DNA replication occurs stochastically in individual cells and, therefore, is not as deterministic as population analyses suggest (Patel et al 2006;Czajkowsky et al 2008). These findings can be reconciled by averaging the heterogeneous replication kinetics of a large number of cells, which recapitulates the observed data from population studies (Czajkowsky et al 2008).…”
supporting
confidence: 66%
“…However, previous genomewide studies of HU-treated cells (Feng et al 2006;Alvino et al 2007), of an rrm3D mutant (Azvolinsky et al 2009), and of a clb5D mutant (McCune et al 2008) do not support this idea. Thus, some aspect of impaired DNA replication that is yet to be elucidated likely accounts for the greatly enhanced frequency of Ty1-Ty1 recombination that forms the HTA2-HTB2 amplification.…”
Section: Discussionmentioning
confidence: 49%
“…Therefore, we measured the amplification frequency after treatment with MMS, a DNA-damaging agent, or HU, which slows DNA replication (Feng et al 2006;Alvino et al 2007). To measure the amplification frequency in wild-type cells, we adapted a previously described method that can detect two copies of the amplified region in a wild-type background, the coq1THIS3 reporter (Figure 2A; Chan and Botstein 1993;Libuda and Winston 2006; see materials and methods for details).…”
Section: Resultsmentioning
confidence: 99%
“…We therefore tested whether, in the cdc7-1 rif1D strain, replication depends on deregulated telomere-proximal origins or genome-wide initiation events. To distinguish between these possibilities, we used an isotopic labeling method (Alvino et al 2007) to monitor the appearance of replicated DNA in the cdc7-1 rif1D strain released from a-factor at 37°C (Fig. 1D, top panel; Supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Genomewide percent replication values were normalized, and the data were smoothed as described (Alvino et al 2007;Feng et al 2009). …”
Section: Microarray Analysis Of Genomic Dna Replication Profilesmentioning
confidence: 99%